Relationships among Elastic Wave Velocities and Stress-Strain Responses in Mortar or Concrete Specimens under Uniaxial Compressive Load: Elastic wave propagation properties of rock materials (mortar or concrete) under load (I) - KOYAMA, Shuhei; NAKAYA, Mitsuo; OKUNO, Hizuru (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1980)
It is well known experimentally that the elastic wave propagation velocity and its amplitude depreciate when the elastic waves encounter cracks in rocks and rocky materials such as concrete and mortar etc. According to various investigators, Gupta (1970), Ito, Omi and Kaneko etal., their observations showed that the propagation velocities and the amplitude in rock specimens under uniaxial compression are altered when the specimens deform. In using the ultrasonic pulsating method, however, little information concerning the observations of concrete or mortar specimens under uniaxial loading has been published. Therefore, in preparing the concrete and mortar specimens, we have attempted to clarify the relationship between the propagation velocity and the characteristics of the deformation in the specimens under the uniaxial compression. The static characteristics of the specimens are obtained from the stress-strain (longitudinal and transverse strain) curves, and the parameters (ΔεT and ΔεV) payed attention to the inelastic region with regard to the stress-strain produced, which are similar to the characteristics of dilatancy in solid rocks noted by Walsh, Scholz, Nur (1972), Brace et al. and Mogi etc. The variations of the incremental transverse strain (ΔεT) and volumetric strain (ΔεV) are suggested to the process from the microfracturing to the main failure in specimens under uniaxial loading.Therefore, the decrease in the longitudinal wave velocity due to incremental strains (ΔεT or ΔεV) can be explained by the wave propagation theory in the two-phase media with cracks based on Walsh's, and Kuster and Toksöz's expressions.